Pengaruh Panjang Batang dan Bentuk Daun Ekor pada Turbin Angin Sumbu Horizontal dengan Mekanisme Furling terhadap Performa Turbin - Hidayatullah, Basori; Al-Janan, Dony Hidayat; Saputro, Danang Dwi (Jurnal Rekayasa Mesin, 2020)
Small-scale wind turbines that operate at low wind speeds regularly will face yawing performance problems. The purpose of this study was to determine the effect of stem length and tail shape on turbine performance through the power generated and the yawing angle and furling angle that formed. An experimental method was used in this research. Tail stem length variations that used were 0.35 m, 0.53 m and 0.71 m. The tail shape varies Rectangular, Trapezoidal, Triangular, Up Rectangular, Down Rectangular, Up Trapezoidal, Down Trapezoidal, Up Triangular and Down Triangular. Wind speed used in this case is 4.3 m/s, 4.8 m/s and 5.2 m/s. The tests carried out at Marina Beach, Semarang. Power measurements using a digital multimeter. Yawing and furling angle measurements using video recordings and measured using Solidworks. Wind speed measurements using a digital anemometer. The results showed that the best configuration is the triangular tail shape with 0,53 m of tail stem length. The power generated of this configuration has increased from wind speed of 4.3 m/s (0.816 Watt) to 4.8 m/s (1.140 Watt) and decreased at a wind speed of 5.2 m/s (1.081 Watt). This phenomenon is related to the design where at wind speed above 5 m/s, the design of furling mechanism will work to reduce the capture of wind energy by diverting the direction of the rotor towards the wind direction. So that the damage of the blade due to higher wind pressure can be minimized.Â